The Effectiveness of Diaphragmatic Breathing Exercise Slow Deep Breathing Musical Therapy and Foot Massage Therapy on Reducing High Blood Pressure in Hypertensive Patiens. Literature Review - Nasrun Pakaya; Anggriani Eka Putri Nento (Global Health Science Group, 2023)
Hypertension is a cerebral vascular disorder where the cerebral blood vessels are narrowed and cause a minimum supply of oxygen and nutrients to brain tissue or blockage. This literature study applied the PICOT framework with Google Scholar, Scien Direct and Scopus databases. It showed a correlation between the effectiveness of diaphragmatic breathing exercise, sloe deep breathing, musical therapy, and foot massage therapy in reducing blood pressure in hypertensive patients of about 80%. In addition, the research proved that diaphragmatic breathing exercise, slow deep breathing, musical therapy, and foot massage therapy effectively reduced blood pressure in hypertensive patients. Through this literature review, slow deep breathing interventions, musical therapy, and foot massage therapy significantly reduced blood pressure, and Diaphragmatic Breathing interventions apart from lowering blood pressure can also reduce anxiety and stress.